Efficient algorithm for replanning web service composition - Kavita D. Hanabaratti; Rudragoud Patil (Institute of Advanced Engineering and Science, 2023)
Web-service-composition (WSC) workload execution inside a hybrid cloud environment is challenging. A dynamic approach for allocating resources to various tasks, as well as associated sub-tasks having a satisfactory quality-ofservice (QoS) requirement, is necessary for the present real-time demand. As a result of focusing primarily on decreasing processing time as well as cost, current approaches improve latency as well as energy while executing a given workload. This study introduces an efficient re-planning (ERP) algorithm for running many scientific workloads inside a heterogeneous cloud environment, which is designed to address some of the shortcomings of previous approaches. With a changing workload, this study details a technique to improve the WSC's availability as well as robustness. The workload's processing energy requirements are reduced as a result. The montageworkflow has been used to validate the research findings. Comparison with the current heterogeneous earliest finish time (QL-HEFT) algorithm demonstrates that its ERP-WSC approach is much more efficient and reliable.